The implication of bilingualism in EFL classroom: An investigation of teaching and learning in English department - Chairuddin Chairuddin; Maulana Yusuf Aditya (Journal of Research on English and Language Learning (J-REaLL), 2021)
Bilingualism is used as a cover term for multilingualism, too - speaking more than two languages. Some researchers use the term plurilingualism for speaking more than two languages. few bilinguals are as proficient in any second language as they are in their first language. This research aims to determine the implication of bilingualism in EFL classroom. Descriptive qualitative is used as a research approach and its application uses phenomenology methods. The findings showed that the implication of bilingualism to students' speaking. The implication is about interact and apply the lecturers' utterance. It can be said this implication related to the students' understanding of the word meaning in speaking. Second implication from the observation data is about students' comprehension in a certain word, such as compounding. The lecturer used bilingualism to explain the meaning of the word. By using Bahasa, the students were easier to understand the lecturer statement. In this case, the students knew what the lecturer's uttered and finally they could know the meaning of the word.